2020
DOI: 10.1115/1.4046908
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Convective Flow of Magnetohydrodynamic Oldroyd 8-Constant Fluid in a Channel With Chemical Reaction and Convective Boundary Condition

Abstract: The present work concentrates on the two-dimensional steady incompressible flow of an Oldroyd-8 constant fluid between vertical plates influenced by a magnetic field. The cross diffusive and second-order chemical reactions are incorporated into the study. The homotopy analysis method (HAM) is used to obtain the series solutions of the transformed system of nonlinear equations. The effects of these parameters on the dimensionless velocity, temperature, concentration, skin friction, and Nusselt and Sherwood numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The authors have molded the nanofluid flow past a stretching curved surface in the presence of chemical reaction, Brownian motion, and thermophoresis. The dimensionless set of flow Equations (19) to (21) along with assisted boundary conditions (22) is solved numerically implementing shooting scheme using RKF45 order technique. The description of RKF45 technique is based on a study by Mishra et al, 27 Mishra and Kumar, 39 and Makinde et al 43 The numerical process is confirmed by doing a comparison with previous findings for θ − ′(0) with different values of Pr.…”
Section: Numerical Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have molded the nanofluid flow past a stretching curved surface in the presence of chemical reaction, Brownian motion, and thermophoresis. The dimensionless set of flow Equations (19) to (21) along with assisted boundary conditions (22) is solved numerically implementing shooting scheme using RKF45 order technique. The description of RKF45 technique is based on a study by Mishra et al, 27 Mishra and Kumar, 39 and Makinde et al 43 The numerical process is confirmed by doing a comparison with previous findings for θ − ′(0) with different values of Pr.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…Generally, RKF45 order technique is used to solve initial value problems (IVPs), thus Equations (19) to (21) are converted to first order. For the present scheme, these equations can be reorganized as…”
Section: Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that a hike in both linear and nonlinear convective parameters enhanced the velocity and temperature profiles but depleted the energy of the system. The MHD Oldroyd 8‐constant fluid flow between vertical plates with chemical reaction was examined by Yusuf et al, 25 who revealed that enhancement in magnetic field strength undermines the flow velocity, temperature, and concentration. The flow of a hyperbolic tangent fluid with the Cattaneo–Christov heat and mass diffusion through a stretching surface was reported by Ibrahim and Gizewu 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Acharya et al 26 scrutinized imprint of aggression kinetics on nanofluid inside channel. Hybrid nanofluid flow within channel was inspected by Acharya, 27 and Yusuf et al 28 scrutinized MHD flow within channel in company of chemical reaction.…”
Section: Introductionmentioning
confidence: 99%